Dark side of the light : slavery and the French Enlightenment - Sala-Molins, Louis (University of Minnesota Press, 2006)
Translated into English for the first time, Dark Side of the Light scrutinizes Condorcet's Reflections on Negro Slavery and the works of Montesquieu, Rousseau, and Diderot side by side with the Code Noir (the royal document that codified the rules of French Caribbean slavery). In doing so, renowned French intellectual Louis Sala-Molins uncovers attempts to uphold the humanist project of the Enlightenment while simultaneously justifying slavery.